Use of brain natriuretic peptide to detect previously unknown left ventricular dysfunction in patients with acute exacerbation of chronic obstructive pulmonary disease (Swiss Medical Weekly, 2011)
BACKGROUND: Up to 30% of patients with chronic obstructive pulmonary disease (COPD) simultaneously suffer from often-unrecognised chronic heart failure (HF). Their timely identification is challenging as both conditions share similar clinical presentations. OBJECTIVE: To assess the performance of BNP in detecting left ventricular systolic dysfunction in patients with no history of HF admitted for acute exacerbation of COPD in a regional second-care hospital. METHODS: Retrospective medical records analysis of all patients hospitalised between January 2003 and May 2009 with the final diagnosis of acute exacerbation of COPD, and who had undergone BNP dosage at admission followed by an echocardiography. RESULTS: Among the 57 patients included, 13 had left ventricular systolic dysfunction. There was a statistically significant difference of mean BNP values between patients with or without systolic dysfunction (mean 689 pg/ml vs. 340 pg/ml, p = 0.007).For the detection of systolic dysfunction, a BNP level inferior to 100 pg/ml yielded a sensitivity of 92% and a negative predictive value of 91%, whereas BNP higher than 500 yielded a sensitivity of 80% and a positive predictive value of 47%. In a multivariate logistic regression analysis, a BNP value ≥500 (odds ratio 8.5, 95% confidence interval 1.9 to 38.2, p = 0.005) and history of coronary heart disease (odds ratio 5.9, 95% confidence interval 1.01 to 34.7, p = 0.048) remained as independent and mutually adjusted predictors of left ventricular systolic dysfunction. CONCLUSIONS:Our study confirms that BNP can help physicians in identifying heart failure in patients suffering from an acute exacerbation of COPD.